Environmental drivers of coccolithophore abundance and calcification across Drake Passage (Southern Ocean) - A. Charalampopoulou; A. J. Poulton; D. C. E. Bakker; M. I. Lucas; M. C. Stinchcombe; T. Tyrrell (Biogeosciences, 2016)
Although coccolithophores are not as numerically common or as diverse in the Southern Ocean as they are in subpolar waters of the North Atlantic, a few species, such as Emiliania huxleyi, are found during the summer months. Little is actually known about the calcite production (CP) of these communities or how their distribution and physiology relate to environmental variables in this region. In February 2009, we made observations across Drake Passage (between South America and the Antarctic Peninsula) of coccolithophore distribution, CP, primary production, chlorophyll a and macronutrient concentrations, irradiance and carbonate chemistry. Although CP represented less than 1 % of total carbon fixation, coccolithophores were widespread across Drake Passage. The B/C morphotype of E. huxleyi was the dominant coccolithophore, with low estimates of coccolith calcite (∼ 0.01 pmol C coccolith−1) from biometric measurements. Both cell-normalised calcification (0.01–0.16 pmol C cell−1 d−1) and total CP (< 20 µmol C m−3 d−1) were much lower than those observed in the subpolar North Atlantic where E. huxleyi morphotype A is dominant. However, estimates of coccolith production rates were similar (0.1–1.2 coccoliths cell−1 h−1) to previous measurements made in the subpolar North Atlantic. A multivariate statistical approach found that temperature and irradiance together were best able to explain the observed variation in species distribution and abundance (Spearman's rank correlation ρ =  0.4, p < 0.01). Rates of calcification per cell and coccolith production, as well as community CP and E. huxleyi abundance, were all positively correlated (p < 0.05) to the strong latitudinal gradient in temperature, irradiance and calcite saturation states across Drake Passage. Broadly, our results lend support to recent suggestions that coccolithophores, especially E. huxleyi, are advancing polewards. However, our in situ observations indicate that this may owe more to sea-surface warming and increasing irradiance rather than increasing CO2 concentrations.